Morphological Characteristics of Cave and Surface-dwelling Ants (Hymenoptera: Formicidae) in Puting Buhangin, Prosperidad, Agusan Del Sur - Michael Jay Mesa (East Asian Journal of Multidisciplinary Research, 2023)
In this study, it was hypothesized that morphological differences were evident between the surface-dwelling and cave ant faunas. There were 9 species of ants found in the study area, namely; Aenictus sp., Anoplolepis gracilipes, Aphaenogaster sp., Carebara sp., Crematogaster sp., Hypoponera sp., Odontoponera sp., Polyrhachis sp., and Tetramorium sp. In this study, limited ant species are present in the cave; in fact, only one species of ant, Aphaenogaster sp., was found in the cave entrance. This study identified no morphological changes between surface-dwelling and cave ants. For accurate data, this research recommends more studies on cave ant morphology.